Integrated Analysis of Key Pathways and Drug Targets Associated With Vogt-Koyanagi-Harada Disease - Chen, Zhijun; Zhong, Zhenyu; Zhang, Wanyun; Su, Guannan; Yang, Peizeng (Frontiers in Immunology, 2020)
Abstract BACKGROUND: Vogt-Koyanagi-Harada (VKH) disease is a complex disease associated with multiple molecular immunological mechanisms. As the underlying mechanism for VKH disease is unclear, we hope to utilize an integrated analysis of key pathways and drug targets to develop novel therapeutic strategies. METHODS: Candidate genes and proteins involved in VKH disease were identified through text-mining in the PubMed database. The GO and KEGG pathway analyses were used to examine the biological functions of the involved pathways associated with this disease. Molecule-related drugs were predicted through Drug-Gene Interaction Database (DGIdb) analysis. RESULTS: A total of 48 genes and 54 proteins were associated with VKH disease. Forty-two significantly altered pathways were identified through pathway analysis and were mainly related to immune and inflammatory responses. The top five of significantly altered pathways were termed as "inflammatory bowel disease", "cytokine-cytokine receptor interaction", "allograft rejection", "antigen processing" and "presentation and Herpes simplex infection" in the KEGG database. IFN-γ and IL-6 were identified as the key genes through network analysis. The DGIdb analysis predicted 48 medicines as possible drugs for VKH disease, among which Interferon Alfa-2B was co-associated both with IFN-γ and IL-6. CONCLUSIONS: In this study, systematic analyses were utilized to detect key pathways and drug targets in VKH disease via bioinformatics analysis. IFN-γ and IL-6 were identified as the key mediators and possible drug targets in VKH disease. Interferon Alfa-2B was predicted to be a potentially effective drug for VKH disease treatment by targeting IFN-γ and IL-6, which warrants further experimental and clinical investigations. Keywords: Vogt-Koyanagi-Harada disease; pathway analysis; network analysis; drug repurposing; uveitis